THE PLACE OF ANALGOSEDATION IN THE MANAGEMENT OF ACUTE ARTERIAL HYPERTENSION IN PATIENT WITH INTRACEREBRAL HEMORRHAGE (REFERENCES) - Gritsenko, S. N.; Davyhora, L. O.; Vorotintsev, S. I. (Modern medical technology, 2022)
The aim of the study. Highlight the most well-founded knowledge that reflects the dependence of treatment and sedation options for patients in the treatment of intracerebral hemorrhage (ICH). Materials and methods. Literature sources related to the study of the annual number of registered stroke cases in the world were analyzed. The vast majority of patients remain permanently disabled, which leads to a decrease in the able-bodied population. An important factor in the development of complications and increased mortality is the high variability and persistent increase in blood pressure (BP). Traditional tactics have a number of disadvantages. At present, there are no clear recommendations for the use of certain antihypertensive drugs, and the optimal numbers to which BP should be lowered are debatable. The results. It has been established that sedation plays an important role in the treatment of intracerebral hemorrhage. In fact, it helps control pain, anxiety, agitation and synchronicity of the patient with the ventilator, and also reduces cerebral metabolic demands and improves the brain’s tolerance to secondary damage. However, combinations of drugs for its implementation may differ even in units of the same hospital. Conclusions. Combination therapy of propofol with opioids or dexmedetomidine with opioids is most common. However, the heterogeneity of the data makes it impossible to qualitatively interpret the obtained results. In turn, due to the uncertainty of the unequivocal tactics of analgosedation, the question of the optimal dosage of drugs is open. Thus, the optimal treatment of acute hypertension in patients with VMC remains a therapeutic dilemma and an important part of scientific research. Adequate correction of the variability of systemic hemodynamics and cerebral perfusion with the help of analgosedation is a promising direction in the treatment of ICH.